A 3 Point Action Agenda to Address Cosmic Hazards and Planetary Defense. Issue 2 (December 2015) - Pelton, Joseph N.
ABSTRACT: The IAASS and the JSSE gives its prime focus to astronaut safety and safe space transport, but one of its important areas of concern is that of cosmic hazards and planetary. This is a significant area because strategies for planetary defense could involve the safety of millions if not billions of people. This article addresses the latest information as to the nature of significant areas of cosmic risks, gaps in our knowledge, and an agenda for research to further planetary in future years. U.K. Royal Astronomer, Sir Martin Rees has noted: "Throughout its history, the Earth has been impacted by asteroids and comets and buffeted by solar flares. But the consequences of these natural phenomena are more catastrophic today, because the infrastructure on which our civilization depends is more elaborate and more vulnerable… …we have instruments, both on the ground and in space, that can give us forewarning of threatening flares and impacts. We are learning how to make our systems more robust and resilient. Moreover, we will not remain helpless in the face of these threats because we are empowered by advancing technology and engineering." (Rees) But despite this quite hopeful statement by the U.K. Royal Astronomer, the truth is that there are many severe planetary risks ahead. Current space agency agendas, space instrumentation, changes to the earth's magnetosphere, and research programs are, in fact, not fully responsive to the needs of a truly effective planetary defense. (Pelton and Allahdadi) This article sets forth some of the greatest lacks in current space programs and notes new or revised efforts that could better prepare our small six sextillion metric ton planet from cosmic dangers. Currently there are several cosmic concerns. These include asteroid and comet strikes from Near Earth Objects, solar flares and coronal mass ejections, and the build-up of orbital space debris that could endanger the safe launch of critical space infrastructure over the longer term future. This article focuses on potentially hazardous comets and asteroids and severe solar storms.